METHODOLOGY OF TEACHING LANGUAGES - Olimova Shaxlobonu Xurshedjonovna (Research Focus International Scientific Journal, 2025)
Language teaching methodologies play a pivotal role in the development of effective communication skills and cultural exchange in our increasingly globalized world. As people from diverse linguistic and cultural backgrounds interact more frequently, the ability to teach and learn languages becomes a central component in fostering understanding, collaboration, and cooperation across borders. Effective language teaching not only empowers individuals to communicate in new languages but also enables them to engage deeply with different cultures, enhancing their global perspective. The evolution of language teaching methodologies has shifted from traditional, teacher-centered approaches to more dynamic, learner-centered techniques. In the early stages of language instruction, methods such as the Grammar-Translation Method dominated, focusing on rote memorization of vocabulary and grammatical rules. Later, communicative approaches gained prominence, prioritizing practical communication skills and the use of language in real-life contexts. In recent years, technological advancements have introduced blended learning and digital tools, reshaping how languages are taught and learned. This paper will explore the various methodologies employed in language teaching, examining their historical development, effectiveness, and practical application in modern classrooms. By evaluating the strengths and weaknesses of traditional, communicative, and innovative methods, this paper aims to highlight how these approaches can be adapted to meet the diverse needs of contemporary learners.